DOPPLER ASSESSMENT OF SPLANCHNIC ARTERIAL FLOW IN PATIENTS WITH LIVER CIRRHOSIS: CORRELATION WITH NITRIC OXIDE - Glisic, Tijana; Popovic, Dusan; Stojkovic Lalosevic, Milica; Martinov, Jelena; Stojanovic, Marija; Jurisic, Vladimir (Medical Research, 2023)
Introduction/aim: Nitric oxide (NO) is a key mediator who, paradoxically, regulated sinusoidal (intrahepatic) and system/splanchnic circulation. The main goal of this study were measurement of NO, comparison of serum values of NO with flow data in visceral blood vessels of the liver, spleen, kidney and intestine in patients with cirrhosis. Material and methods: This prospective study included 80 patients with liver cirrhosis. Doppler ultrasonography was used to assess flow velocity and resistive index (RI) in the hepatic (HA), right (RRA), and left renal (LRA), splenic (SA) and superior mesenteric artery (SMA). NO concentration was determined using the DetectX® Nitric Oxide colorimetrically detection kit. Results: We find a statistically significant difference in the mean NO value in the group of patients without ascites compared to the ascites group, and also  in the group of patients with A stage in relation to the C stage of liver cirrhosis (p
Keywords: liver cirrhosis; nitric oxide; Doppler ultrasonography